Board Functions and Firm Performance:: A Review and Directions for Future Research - Ong, Chin; Lee, Soo (Journal of Comparative International Management, 2000)
This study provides a framework depicting the evolution of studies on the functions of boards of directors and their impact on firm performance. Four theories-legalistic, strategic choice, agency, and stewardship theory-are linked to describe the relationships in the evolution process underlying this phenomenon. From this review, directions for future research are identified.